Faktor Pendukung dan Penghambat dalam Penerapan Pilar Fasilitas Sekolah Aman Bencana di Kecamatan Koto Tangah Kota Padang - Azirah, Nurul; Alhadi, Zikri (YASIN, 2025)
This study is motivated by the critical importance of implementing Pillar 1 of the Safe School Program (Satuan Pendidikan Aman Bencana or SPAB), which focuses on disaster-resilient school facilities as the foundation for protecting school communities—especially in disaster-prone areas such as Koto Tangah District, Padang City. Although the SPAB program has been implemented, several challenges persist, particularly concerning physical infrastructure, such as the lack of adequate evacuation routes and school buildings that do not meet earthquake-resistant standards. This study aims to identify supporting and inhibiting factors in the implementation of the Disaster-Resilient Facility Pillar at the elementary and junior high school levels in the region. A qualitative approach was employed, with data collected through in-depth interviews, field observations, and document analysis. The findings reveal that supporting factors include school commitment, basic disaster mitigation awareness, and technical assistance from the Regional Disaster Management Agency (BPBD). Conversely, inhibiting factors consist of limited budget allocation, infrastructure that does not meet safety standards, and the absence of structured technical guidelines. The study concludes that strengthening policy frameworks and fostering cross-stakeholder collaboration are essential for the development of disaster-resilient school infrastructure. The implications contribute to disaster-related literature in the education sector and serve as a reference for enhancing the effectiveness of SPAB implementation in disaster-prone regions.